Wire-arc directed energy deposition of martensitic stainless steel hardfacing alloy: Microstructure and abrasion wear resistance - Alireza Khaghani; Majid Pouranvari (Journal of Materials Research and Technology)
Fe–Cr–C martensitic stainless steels serve as essential hardfacing alloys in applications where abrasion resistance is critical to the performance of components. This study employs a multi-track, multi-layer wire-arc directed energy deposition (WA-DED) technique to deposit ER420 martensitic stainless steel hardfacing alloy onto an AISI 4140 substrate. The investigation focuses on exploring the relationship between the microstructure of the hardfacing layer and its hardness, tensile properties, impact toughness, and wear behavior under dry sand rubber wheel testing conditions. Counterintuitively, it was found that applying a post-deposition tempering thermal treatment significantly enhances the abrasion resistance of the hardfacing layer, albeit at the cost of reducing its hardness. In the as-deposited state, the top layer exhibits dual regions of untempered and tempered martensite, with δ-ferrite present along sub-solidification boundaries. This configuration imparts high hardness to the hardfacing layer but compromises its toughness, resulting in a pronounced abrasion wear rate through a micro-cutting/micro-cracking mechanism. However, enhancing the toughness of the hardfacing through an appropriate post-deposition tempering process shifts the wear mechanism from micro-cutting/micro-cracking to micro-ploughing, leading to a significant improvement in wear resistance. This study emphasizes that both fracture toughness and hardness are critical factors for optimizing the performance of abrasion-resistant hardfacing alloys.